Analyzing telework, trustworthiness, and performance using leader-member exchange COVID-19 perspective - Brown, Michael A. (IGI Global, 2022)
"Useful for people and organizations seeking answers to COVID-related issues of teleworking, this book a new look at teleworking, an examination of important factors, and a plan for improvement in the short and long term.
Includes bibliographical references and index
Section 1. Examining telework and contributing factors. Chapter 1. Teleworking ; Chapter 2. Our changing world ; Chapter 3. LMX theory ; Chapter 4. Trustworthiness ; Chapter 5. Performance -- Section 2. Understanding leadership and related factors to telework. Chapter 6. Leadership ; Chapter 7. Motivation ; Chapter 8. Productivity ; Chapter 9. Emotional intelligence (EI) ; Chapter 10. Radical change -- Section 3. Analyzing the data to facilitate fact-based decisions. Chapter 11. Teleworking research ; Chapter 12. Recommended approaches ; Chapter 13. The future. - Mode of access: World Wide Web
Keywords: Telecommuting; COVID-19 Pandemic, 2020-